An Online Reservation and Food Ordering System for Arabian House Restaurant - AL-seaghi, Mazen Hamoud Mohammed; Ghazali, Rozaida (Applied Information Technology And Computer Science, 2022)
Online Reservation and Food Ordering System will greatly simplify the reservation and ordering process for both the customer and the restaurant. Before the adaptation of reservation systems, many people had to change their choice of restaurant or food because the restaurants were full and there was a lot of disappointment involving the management of the restaurant. The website presents an interactive and up-to-date schedule for the daily reservation and ordering with all available options in an easy-to-use manner. Customers can choose the better reservation type and food to visit the restaurant which will lead to choosing the suitable day and time for him/her to make the reservation or order. This allows restaurant staff to easily manage the reservation and ordering and serve the customer efficiently and effectively with minimal time and effort consuming for both customers and staff. To achieve the objectives, the use of PHP and HTML programming and prototype models that allows repeated development processes in the analysis phase, design phase, and implementations phase was used to create a system that wanted to be developed. Test system modules will be performed after the website has been fully developed. The reliability of the system is important by the results of the tests to make changes to ensure that the system being built operates correctly and to ensure that the goals have been accomplished. The system will facilitate the customers to make a reservation and order easily by entering their information and choosing the appropriate time for visiting the restaurant. Therefore, this website also will help with the schedule to avoid crowds inside the restaurant by receiving a limited number of customers per day. In addition to that, the website will provide information and location about the restaurant for customers.